Passively Pitching Blades for Tidal Turbines: Design and Modelling (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Faced with inherent flow unsteadiness in their operational environments, most horizontal-axis tidal turbine designs employ blade-pitch control to mitigate load fluctuations and to cap the maximum power transmitted to the generator when the flow speed is above the rated speed. A novel method of passive pitch control has been proposed (https://doi.org/10.36688/imej.5.183-193)  as a method for reducing load fluctuations without affecting mean values, pointing to the promise of decreased fatigue while maintaining constant power production in variable flow fields. In this paper, we expand on available work  (https://doi.org/10.1016/j.jfluidstructs.2024.104216 ; https://doi.org/10.1016/j.renene.2024.121921) to investigate the capabilities of a low-order numerical model of capturing the physics of pitching blades in turbulent flow fields.To this end, we have developed a Simulink code coupled with OpenFAST, an open-source code based on blade element momentum theory. We show that the computed mean and statistics of rotor torque and thrust are in good agreement with those experimentally measured for a 1.39-meter-diameter turbine equipped with a passive pitch (see the paper "Passively Pitching Blades for Tidal Turbines: Experimental Demonstration" by Sunil et al. within this conference for details on the experiments). The numerical model additionally considers a discretised 2-dimensional flow field informed by flow characteristics of the testing facility (FloWave Ocean Energy Research Facility), measured using acoustic Doppler velocimetry and fitted to a Von Kármán spectrum. The use of a 2-dimensionally resolved field coupled with the low-order numerical model accounts for and identifies significant loading frequencies and their mitigation as observed experimentally for fixed and passively pitching turbines; information otherwise not captured by simpler models.Experimental validation of the model demonstrates its capability as a tool used in the design process of passively pitching systems, suitable for fast prototyping, and exploring the capabilities and limitations of such systems.